Conditions associated with discarding of blood and its components in a blood bank of tertiary care hospital of Western Uttar Pradesh: a retrospective study - Singh, Preeti; Singh, Neha; Thakur, Anamika Singh; Gautam, Akanksha (International Journal of Research in Medical Sciences, 2024)
Background: Blood transfusion services in India rely on different factors for a smooth workout. Thus proper utilization of blood is necessary with minimal wasting. The aim was to evaluate the causes of discarding of blood and its components and to implement possible intervention for minimizing wastage. Methods: A retrospective study was carried out in the blood bank of Sardar Vallabh Bhai Patel Hospital, Lala Lajpat Rai Medical College, Meerut, Uttar Pradesh over a time period of 24 months from April 2019 to March 2021. Results: A total of 21627 units were collected from donors. A total of 11534 whole blood (WB), 10093 packed red blood cells (PRBC), 3245 platelets (PC), and 9669 fresh frozen plasma (FFP) were prepared. A total of 4046 units of blood and its components were discarded. The discard rate for WB, PRBC, PC and FFP was 6.25%, 7.46%, 38.39%, and 13.71% respectively. Conclusions: An average of 18.70% of blood units were discarded during this study period. The overall most common reason for discard was the date of expiry followed by transfusion transmitted infections (TTI). To minimize wastage of blood units, blood banks should be fully committed to organizing and coordinating the blood transfusion services,implementing all possible strategies as discussed in order to lower the discarding of blood and its units and to make them widely available.